The vocabulary of agriculture semi-popularization articles in English: A corpus-based study - Muñoz, Verónica Lilian (2015)
Scientific communication can be represented as a continuum with the research article, addressed to specialized researchers, at one end of the spectrum, and with the popularization article, addressed to lay readers, at the other. In between there exists a distinct genre, the semi-popularization article, which has not received much attention in the English literature. As a contribution to the field, this paper describes the vocabulary of a corpus of 700 agriculture semi-popularization articles in English. The analysis was carried out in two stages that combined quantitative and qualitative methodology: a lexical description of the corpus and the analysis of high-frequency words. The lexical analysis revealed high lexical variation in the corpus and narrow word range. Academic words provided a lower coverage (6%) than that usually reported for research articles (10-12%), and a higher coverage than that reported for newspapers (4%). The analysis of high-frequency words showed that many of these words, including general and academic words, were closely associated with the discipline of agriculture, and therefore represented the technical vocabulary of the texts.